The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1155/2015/261802
|View full text |Cite
|
Sign up to set email alerts
|

Biological Behaviour and Enhanced Anticorrosive Performance of the Nitrided Superelastic Ti-23Nb-0.7Ta-2Zr-0.5N Alloy

Abstract: The influence of gas nitriding surface treatment on the superelastic Ti-23Nb-0.7Ta-2Zr-0.5N alloy was evaluated. A thorough characterization of bare and nitrided Ti-based alloy and pure Ti was performed in terms of surface film composition and morphology, electrochemical behaviour, and short term osteoblast response. XPS analysis showed that the nitriding treatment strongly influenced the composition (nitrides and oxynitrides) and surface properties both of the substrate and of the bulk alloy. SEM images revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…These observations have revealed the typical appearance of osteoblast cells with well-expressed stress fibers oriented parallel to one another and to the long axis of the cell and punctiform vinculin signals at the termini of actin microfilament bundles. On the other hand, no significant differences in terms of cell spreading, cytoskeleton organization, and focal contact formation could be observed between Ti-23Nb-0.7Ta-2Zr-0.5N and CP-Ti [29]. Taken together, these findings prove that the studied Ti-23Nb-0.7Ta-2Zr-0.5N alloy favors cell proliferation without showing any deleterious effect suggesting increased biocompatibility.…”
Section: In Vitro Behavior Of Human Osteoblastssupporting
confidence: 52%
See 2 more Smart Citations
“…These observations have revealed the typical appearance of osteoblast cells with well-expressed stress fibers oriented parallel to one another and to the long axis of the cell and punctiform vinculin signals at the termini of actin microfilament bundles. On the other hand, no significant differences in terms of cell spreading, cytoskeleton organization, and focal contact formation could be observed between Ti-23Nb-0.7Ta-2Zr-0.5N and CP-Ti [29]. Taken together, these findings prove that the studied Ti-23Nb-0.7Ta-2Zr-0.5N alloy favors cell proliferation without showing any deleterious effect suggesting increased biocompatibility.…”
Section: In Vitro Behavior Of Human Osteoblastssupporting
confidence: 52%
“…By day 5, the proliferation rates on the two surfaces were significantly higher than those found after 1 and 3 days of culture. In a very recent study [29], we have observed on the Ti-23Nb-0.7Ta-2Zr-0.5N alloy the cell-to-substrate interaction by double fluorescent staining of vinculin and actin filaments. These observations have revealed the typical appearance of osteoblast cells with well-expressed stress fibers oriented parallel to one another and to the long axis of the cell and punctiform vinculin signals at the termini of actin microfilament bundles.…”
Section: In Vitro Behavior Of Human Osteoblastsmentioning
confidence: 91%
See 1 more Smart Citation
“…For this, the pre-osteoblast cells grown on the above substrates were fixed, permeabilized, blocked and incubated with specific antibodies, as previously reported. 53 Subsequently, phalloidin coupled with Alexa Fluor 488 was added in order to label actin filaments and, then, 4′,6-diamidino-2-phenylindole (DAPI) to visualize the nuclei. Labelled samples were washed three times with PBS and examined under an inverted microscope equipped with epifluorescence (Olympus IX71).…”
Section: Methodsmentioning
confidence: 99%